Industrial training report: Management Services and Human Resources Department (MylPO) / Mastura Md Zali - Md Zali, Mastura (Bachelor of Information Science (HONS.) Records Management, 2015)
The academic writing report paper is based on the period of Industrial Training (IMC690) from 4 February 2015 until 30 June 2015 in Intellectual Property Corporation of Malaysia (MylPO). The report is carried out based on Industrial Training that have be made by Mastura binti Md Zali a student Semester 7 of Bachelor of Information Science (Hons.) Records Management (IM246). By doing the industrial training, it made the student expose with the real environment of the working areas. Besides that, student is able to understand the functions and activities that the organization provides such as gives protection towards the intellectual property in Malaysia. Thus, can made the student be able to work in a teamwork and be a part of the agency during the industrial training.